2023
DOI: 10.1186/s12950-023-00342-1
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated endothelial cell markers in systemic lupus erythematosus: a systematic review and meta-analysis

Abstract: Objectives To perform a systematic literature review and meta-analysis on endothelial cell (EC) markers that are involved and dysregulated in systemic lupus erythematosus (SLE) in relation to disease activity, as EC dysregulation plays a major role in the development of premature atherosclerosis in SLE. Methods Search terms were entered into Embase, MEDLINE, Web of Science, Google Scholar and Cochrane. Inclusion criteria were 1) studies published a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…ECs are important for regulating blood pressure and play important roles in coagulation, fibrinolysis, angiogenesis, and immune cell activation via both physiological and pathological processes [ 99 ]. The modulation of endothelial cells via the adaptive and innate immune systems plays an integral role in autoimmune diseases, as endothelial cells promote chronic inflammation via angiogenesis, attracting immune cells, and antigen presentation [ 100 ]. Anti-endothelial cell antibodies (AECA) are a heterogeneous group of autoantibodies directed against structural endothelial proteins, along with antigens on endothelial cells [ 101 ].…”
Section: Autoantibodies Can Lead To Neuronal Damage In Npslementioning
confidence: 99%
“…ECs are important for regulating blood pressure and play important roles in coagulation, fibrinolysis, angiogenesis, and immune cell activation via both physiological and pathological processes [ 99 ]. The modulation of endothelial cells via the adaptive and innate immune systems plays an integral role in autoimmune diseases, as endothelial cells promote chronic inflammation via angiogenesis, attracting immune cells, and antigen presentation [ 100 ]. Anti-endothelial cell antibodies (AECA) are a heterogeneous group of autoantibodies directed against structural endothelial proteins, along with antigens on endothelial cells [ 101 ].…”
Section: Autoantibodies Can Lead To Neuronal Damage In Npslementioning
confidence: 99%
“…ECs are important for regulating blood pressure and play important roles in coagulation, fibrinolysis, angiogenesis, and immune cell activation via both physiological and pathological processes [80]. Modulation of endothelial cells via the adaptive and innate immune systems plays an integral role in autoimmune diseases, as endothelial cells promote chronic inflammation via angiogenesis, attracting immune cells, and antigen presentation [81]. Antiendothelial cell antibodies (AECA) are a heterogeneous group of autoantibodies directed against structural endothelial proteins, along with antigens on endothelial cells [82].…”
Section: Structural Endothelial Proteins (Aeca)mentioning
confidence: 99%
“…This means that small changes in its concentration influence physiological effects [4,15]. Some research has shown that the serum concentration of VEGF corresponds with the clinical activity of various diseases, including tumor growth, atherosclerosis of the coronary arteries, Kawasaki disease, neovascularization of synovial tissue in rheumatoid arthritis and diabetic microangiopathy [16][17][18][19]. In patients with DM1, hyperglycemia stimulates VEGF upregulation.…”
Section: Introductionmentioning
confidence: 99%